T(x)=3x-6/2x*(x-1)

Simple and best practice solution for T(x)=3x-6/2x*(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for T(x)=3x-6/2x*(x-1) equation:



(T)=3T-6/2T(T-1)
We move all terms to the left:
(T)-(3T-6/2T(T-1))=0
Domain of the equation: 2T(T-1))!=0
T∈R
We multiply all the terms by the denominator
T*2T(T-1))-(3T-6=0
Wy multiply elements
2T^2(T-6=0

See similar equations:

| 90=2/3x-60 | | 0.5x-0.6x+7=-9 | | 2x-19=x=11 | | 2(3x-4)+3(2x-3)=-2(x+5) | | 0.05x-0.6x+7=-9 | | 5x−9=15+11x | | 17-5y=17 | | k/2+9=3- | | 14=x2+7 | | 6+5(x-1)=36 | | x6=198 | | X^2+6x+11=x+5 | | y+y+y+y+-13637=173663737 | | 2.8p=112 | | 6+5(x-1=36 | | 3/4x-17+3x-13=90 | | X^2+2x-1=x+1 | | p-0.2p=0 | | -41/3=a-31/3 | | 2n+14=3n-5 | | 3/4x-17-3x-13=90 | | 7(n+11)=4n | | 2^t=14 | | X^2-2x+6=3x+2 | | X^2+x=x+1 | | 1/2=k(4) | | -2(x-3)+8x=9x-8 | | 14x^+×-3=0 | | X^2+3x+1=x+4 | | X^2+x+1=2x+1 | | 36x^2=28 | | -5/8+x=-5/8 |

Equations solver categories